2011
DOI: 10.1063/1.3636417
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Zr0.5Hf0.5O2 thin films for nonvolatile memory applications

Abstract: We report the observation of ferroelectricity in capacitors based on hafnium-zirconium-oxide. Hf0.5Zr0.5O2 thin films of 7.5 to 9.5 nm thickness were found to exhibit ferroelectric polarization-voltage hysteresis loops when integrated into TiN-based metal-insulator-metal capacitors. A remnant polarization of 16 μC/cm2 and a high coercive field of 1 MV/cm were observed. Further proof for the ferroelectric nature was collected by quasi-static polarization-voltage hysteresis, small signal capacitance-voltage, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
269
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 487 publications
(299 citation statements)
references
References 14 publications
6
269
0
2
Order By: Relevance
“…To assess the phase stability at a finite temperature T and entropy S, we calculated the Helmholtz free energy F as F = U -TS (2) from the phonon contribution by integrating over the phonon density of state. …”
Section: H Elm Holtz Free Energymentioning
confidence: 99%
“…To assess the phase stability at a finite temperature T and entropy S, we calculated the Helmholtz free energy F as F = U -TS (2) from the phonon contribution by integrating over the phonon density of state. …”
Section: H Elm Holtz Free Energymentioning
confidence: 99%
“…In this connection, anisotropic stresses are required for the phase transition from tetragonal to orthorhombic, i.e., a compressive stress within the aob plane and a tensile stress along the c-axis exerted on the t-phase. There are many factors reported hitherto to be responsible for causing the anisotropic stresses and thus stabilizing the ferroelectric o-phase during the film growth, such as doping, 4,5,[23][24][25][26][27][28][29][30][31][32][33][34][35] surface energy effect, [36][37][38] island coalescence, 39 thermal expansion mismatch, 17 capping layer effect, 4,38 and formation of oxygen vacancies. 40 The following of this section will discuss each of these factors in order.…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
“…Recently, it has been demonstrated that doping of HfO 2 thin films with SiO 2 5 or ZrO 2 6 does not only stabilizes the tetragonal phase, but can also produce a spontaneous polarization at intermediate doping levels, that results in usable, ferroelectric hysteresis loops in these layers.…”
Section: Introductionmentioning
confidence: 99%